Local Cultural Aspects In The KBSM English Language Materials - Zakaria, Mohamad Hassan; Mohd Hashim, Nursophia Hasdina (2010)
Malaysian students come from various ethnicities and cultural communities since Malaysia is known as a multiracial and multicultural country. Therefore, issues related to the portrayal of local cultural aspects in KBSM English Language materials used in some Malaysian schools have captured the attention of researchers. This study employs a set of checklist which has been used as a guideline to analyze the cultural aspects in a curriculum in order to examine English Language Form 1 to Form 5 textbooks used in schools in Johor Bahru. The findings show that there was insifficient incorporation of cultural aspects into the English materials. Many of the available cultural elements were presented at a superficial level and not discussed within the holistic cultural experience. The findings suggest that the absence and the lack of certain cultural aspects in the materials may be due to the fact some cultural topics are avoided fearing sensitivity, and that they may be implicitly portrayed through, for example, value integration, moral and educational emphasis. This study recommends that language learning materials must be able to present the language learners’ own culture and all the cultures that suround them and the materials must be useful and effective both as English learning materials as well as a tool for promoting cultural knowledge and understanding among Malaysian students.